The Relation Between Extracellular Vesicles Released From Red Blood Cells, Their Cargo, and the Clearance by Macrophages - Nguyen, Duc Bach; Tran, Hanh Triet; Kaestner, Lars; Bernhardt, Ingolf (Frontiers in Physiology, 2022)
Extracellular vesicles (EVs) are cell-derived membrane particles including exosomes, ectosomes, microvesicles, microparticles, apoptotic bodies and other EV subsets. EVs are involved in intercellular communication and the transport of macromolecules between cells. Here we propose and test the ability of RBC-derived EVs (RBC-EVs) as putative drug carriers. EVs were produced by treating RBCs with Phorbol-12-myristate-13-acetate (PMA) and separated from the cells by differential centrifugation steps. RBC-EVs were characterized by size determination, flow cytometry and scanning electron microscopy (SEM). EVs were loaded with DNA plasmids coding for the green fluorescent protein (GFP) by electroporation. The DNA loaded EVs (DNA-EVs) were used to transfect THP-1 derived macrophages and analysed by fluorescence microscopy and flow cytometry. The results showed that RBC-EVs had an almost spherical shape and a polydispersity in their size with an average of 197 ± 44 nm and with a zeta potential of -36 ± 8 mV. RBC-EVs were successfully loaded with DNA but associated with an increase of the polydispersity index (PdI) and showed a positive signal with Picogreen. DNA-EVs were almost completely taken up by macrophages within 24 h, however, resulting in the expression of the GFP in a subpopulation of macrophages. As the way we designed, RBC-EVs could be potential nucleic acid carriers when the immune system was addressed. This study may contribute to the understanding of the role of EVs in the development of microvesicle-based vehicles.